Cardia Laxity under Retroflexed Endoscopy Is a Reflection of Esophageal Hiatus Enlargement - Dong Chen; Shurui Tian; Zhiwei Hu; Jimin Wu (Gastroenterology Research and Practice)
Background and Aim. In clinical practice, we found that the degree of gastroesophageal laxity (cardia or hiatus) under retroflexed endoscopy is associated with the enlargement of esophageal hiatus during operation, but specific data was lacking. The aim of this study was to confirm this correlation. Methods. Information from patients who underwent endoscopy and CT scan in our department was collected and analyzed retrospectively. Three-dimensional reconstruction of hiatus from CT images was performed using 3DSlicer software, and the degree of esophageal hiatus enlargement was compared with the degree of gastroesophageal laxity under retroflexed endoscopy. Results. Information from 104 patients was included for analysis. The Spearman correlation coefficient was 0.617 (p≤0.001). When subgroup correlation analysis was performed according to the presence of hiatal hernia on CT, the Spearman correlation coefficient was 0.816 (p≤0.001) in the hernia group and 0.351 (p=0.002) in the nonhernia group. The proportion of hiatal hernia and severe esophagitis was increasing gradually with the degree of gastroesophageal laxity. Conclusion. The degree of gastroesophageal laxity (cardia or hiatus) under retroflexed endoscopy reflects the degree of esophageal hiatus enlargement; with the degree of gastroesophageal laxity increasing, the proportion of HH and severe esophagitis increases gradually. This may be useful for physicians in China to guide themselves in the selection of patients for endoscopic antireflux treatment.